A comparative analysis between in Vitro and in Vivo generated insect forms of trypanosoma congolense. - Chepkorir, M.N. (University of Nairobi, 1995)
Biological processes, such as the cell-division, differentiation and development, are driven by changes in gene expression. It is therefore important to examine the molecular processes involved in the differentiation and development of trypanosomes since the products of developmentally regulated genes which control these processes present potential targets for intervention and control of trypanosomiasis. Expression of developmentally expressed genes in the trypanosome however, is significantly influenced by alterations in the external environment, such as temperature and nutrients. The different developmental stages of Trypanosoma congolense are propagated in vitro under different conditions, and current systems can generate sufficient numbers for molecular and biochemical studies. This material is central to current studies at ILRAD on parasite differentiation and proliferation. However, in vitro conditions for the propagation of the different life cycle stages differ substantially from the in vivo conditions, and it is important to determine whether differentially expressed sequences identified from in vitro generated material also show the same expression profiles in vivo. To determine whether differences do occur between the in vivo and in vitro generated trypanosomes, procyclic forms from T.congolense IL1180 were isolated from infected tsetse flies and culture. Total RNA was purified from both populations of parasites. Enrichment of polytA)" RNA from both populations was carried out followed by first strand cDNA synthesis in the presence of reverse transcriptase and oligo(dT). A portion of both cDNAs was used a~the template inPCR reactions designed to specifically amplify cDNA of trypanosome origin with primers which exploit the conserved 5' splicedleader and 3' poly(A) sequences found on alltrypanosome mRNAs characterised to date. Following removal of these primers and dNTPs, the resultant double-stranded cDNAs were used as templates in a new technique developed at ILiAD termed "random amplified differentially expressed sequences". The RADES-PCR analysis was carried out with 10-mer arbitrary primers. The majority of primers generated fingerprints which were similar or identical for both cDNA templates. To ensure that the RADES-PCR products were of trypanosome rather than tsetse fly origin, Southern blots of the products were probed with total labelled trypanosome genomic DNA. Further confirmation of the specificity of the RADES-PCR products specifically amplified from in vitro or in vivo derived material was achieved through probing of Southern blots with labelled cDNA from the two sources. Some ofthe differentially amplified products were cloned and sequenced. One of the in vivo-specific products was of particular interest, since it displayed a significantly higher level of expression in the in vivo generated parasites, but did not display differential expression between the different in vitro generated life cycle stages, or between in vivo derived bloodstream forms and the life cycle stages. Sequence analysis of the cloned product revealed an apparently bi-functional gene product with significant homology in one domain to the eukaryotic L19 ribosomal gene product and in another domain to proteases, particularly serine proteases. An in vitro-specific product was also sequenced, but no homologue was found in the current DNA sequence databases and expression of this product was difficult to detect both in vitro and in vivo. In conclusion, use of the RADES-PCR method has demonstrated that differences in gene expression between in vivo and in vitro parasites do occur. The method was particularly useful in these studies, since the in vivo derived material contained predominantly host material, yet the cDNA sequences of trypanosome origin were easily and selectively amplified.